2013
DOI: 10.15580/gjms.2013.2.012013398
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Medicinal Values ofRauvolfia vomitoria (Afzel) in Ibadan Municipality

Abstract: Naturally inherited herbs are almost lost and only very few are left in the herbal trade. The study therefore assessed the medicinal values of Rauvolfia vomitoria and its availability in Ibadan municipality with the use of structured questionnaires and target informant interview. A multistage sampling procedure was used to collect data on medicinal values of Rauvolfia vomitoria. Data collected were analyzed using descriptive and cross tabulation. The findings revealed that Rauvolfia vomitoria has a lot of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The extract of R. vomitoria has been used as traditional medicine for over 2000 years in Africa for the treatment of hypertension and mental disorders and recent studies have confirmed its effectiveness as antipsychotic, antihypertensive, and anti-inflammatory agent and for improving blood chemistry. In Ghana, root specimens of R. vomitoria are used as emetic and purgative and to treat parasitic skin diseases [ 22 ] and jaundice and gastrointestinal disorders [ 23 ]. It was reported that the bark of R. vomitoria can be used against such parasites as lice and scabies.…”
Section: Introductionmentioning
confidence: 99%
“…The extract of R. vomitoria has been used as traditional medicine for over 2000 years in Africa for the treatment of hypertension and mental disorders and recent studies have confirmed its effectiveness as antipsychotic, antihypertensive, and anti-inflammatory agent and for improving blood chemistry. In Ghana, root specimens of R. vomitoria are used as emetic and purgative and to treat parasitic skin diseases [ 22 ] and jaundice and gastrointestinal disorders [ 23 ]. It was reported that the bark of R. vomitoria can be used against such parasites as lice and scabies.…”
Section: Introductionmentioning
confidence: 99%
“…They further reported that a watery solution of the bark of R. vomitoria can be used against such parasites as lice and scabies. R. vomitoria is employed in the treatment of rheumatoid arthritis (Fapojuwomi and Asinwa, 2013). Sharma (2004) added that the root of R. vomitoria is good for the treatment of snake bites, insect stings, nervous disorders, mania, epilepsy, intractable skin disorders such as psoriasis, excessive sweating, itching, hypertension, sedative, uterine contraction in child birth and gynecological ointment for the treatment of menopausal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Most alkaloids have found their way in medicinal application as antimalarial, antimicrobial , antibacterial, antifungal and antiparasitic activities . Most samples containing alkaloid are used in Nigeria for the treatment of malaria and fever (14,12). Alkaloids are the most efficient therapeutically significant plant substance.…”
Section: Gc-ms Experimental Proceduresmentioning
confidence: 99%